Low-cost I-V tracer for photovoltaic modules and strings - Leite, Vicente (2014)
This paper presents new developments of a robust and low-cost instrument-less than 600 (sic)-for monitoring and processing I-V and P-V characteristics of photovoltaic (PV) modules and high voltage strings. The characteristics can be traced on an oscilloscope or using a developed a LabVIEW application. It is a simple instrument because only fundamental electronic circuits are used. The equipment consists of a flexible configuration, developed from a previous work, based on a fast varying load based on a power MOSFET. The MOSFET was controlled by means of suitable gate-source voltage control signal in order to improve the tracing of I-V and P-V characteristics on an oscilloscope. The contribution of this work includes new developments of a previous I-V tracer in order to be use with high voltage strings and a low-cost DAQ monitoring system based on two applications developed in LabVIEW-one for PV modules and the other for PV strings. On the other hand, the robustness for high voltage strings was strongly improved in view of field tests for fault diagnosis analysis. Experimental results obtained with the new instrument are presented with modules and different strings available with voltages up to 1000 volt.